Description Of Social Interaction Elderly In Kuta Raya Village: Social Interaction Elderly - Kaban, Indriani Christine; Simorangkir, Lindawati; Novitarum, Lilis (STIKes Mandala Waluya Kendari, 2024)
Background: Social interaction of the elderly is negative because there is no good relationship orcommunication between the elderly, family, peers and their environment. Caused by the physical and pshychological liminatinons of the elderly. This study aims to describe the social interaction of the elderly in Kuta Raya Village 2023 Methods: Used descriptive with a cross sectional approach. The population in this study are all the elderly in Kuta Raya Village, totaling 105 elderlies. The sampling technique in this study is simple random sampling, with a total sample of 51 respondent. Collecting data using a questionnaire containing 20 statements. Results: Social interaction of the elderly based on the on the cooperation indicator in Kuta raya Village 2023 is found to be (58,8%) enough. The social interaction of elderly based competition indicators is found to be (64,7%) enough. The social interactionsof elderly based on indicators of conflict were (100%) good, and the social interactions of elderly based on indicators of conformity were obtained (98,0%) good. Conclusions: It is expected that the elderly will take part in Posyandu and elderly gymnastics to increase the social interaction of the elderly.